WAGE DIFFERENTIALS IN THE CZECH AGRICULTURAL SECTOR IN THE PERIOD OF THE 1ST QUARTER 2000 TO THE 3RD QUARTER 2012 AND LABOR PRODUCTIVITY - Marta Grycova (European Scientific Journal, ESJ, 2014)
Long lasting wage disparity in agriculture has a negative effect on the number of workers in this sector and thus rural demographic development. The causes of the external income disparities in the agricultural sector according to economic theories have changed over time and currently each determinant of wage disparities in agriculture reaches a significance of various sizes. This paper carries out the calculation of the gross external wage disparities in the agricultural sector compared to the values for the total economy. The main objective of this paper is to estimate the significance of the influence of labor productivity in agriculture, calculated as the ratio of gross value added and total employment in the agricultural sector, on wages in agriculture using linear regression model of the 1st differences of the variables, estimated by ordinary least squares method. One solution could be to increase the labor productivity.